RESPON FISIOLOGIS IKAN PATIN SIAM (Pangiasanodon hypothalmus) PADA BERBAGAI TINGKAT KALSIUM MEDIA - Muliani Muliani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
Calcium is one of macromineral that needed by fish for physiological processes such as osmoregulation, enzyme regulation, ossification and cell permeability. This study aimed to determine the optimum concentration of calcium carbonate (CaCO3) at 3 ppt salinity of media and evaluated the effects of adding calcium to physiological conditions. The study was conducted in two stages; the first stage was determined the optimum concentration of calcium, the second stage was evaluated the effect of calcium on the physiological condition of fish. Randomized completely design with four treatments and three replication; 3 ppt + 0 mg/L CaCO3, 3 ppt + 50 mg/L CaCO3, 3 ppt + 100 mg/ L CaCO3, 3 ppt + 150 mg/L CaCO3, were used in this study. The results showed that the salinity of media with the addition of calcium can reduce levels of osmotic performance, oxygen consumption, and blood glucose levels. Treatment 3 ppt + 100 mg/L showed the best physiological condition among other treatments.